Beyond BMI: The Janus-like effect of muscle versus fat on midlife women’s health - Eu-Leong Yong; Beverly Wen Xin Wong; Darren Yuen Zhang Tan (Annals, Academy of Medicine, Singapore)
Janus—the Roman goddess of natural cycles, change and transitions—is an appropriate symbol for the life-changing shift from the reproductive period to the post-menopausal stage of life. Since the average age of menopause is 50 years,1 it is a universal life stage for long-living Singaporean women. The menopausal transition is associated with a profound decline in circulating oestrogen levels, resulting in the slowing of basal metabolism and marked changes in body composition.2 On average, women gain approximately 2 to 3 kg during the menopause transition. Remarkably, many Singaporean women maintain relatively stable “healthy” BMI, even though deleterious changes in their body composition are occurring.2 These changes in body composition involve 2 variables, both of which increase BMI. However, 1 variable has positive, while the other has negative health effects. Muscle mass/strength—a positive factor that increases BMI—is necessary for cardiometabolic and skeletal health, activities of daily living and mobility.3 Lack of muscle mass, or sarcopenia, results in frailty and increased risk of death.3 On the other hand, abdominal (visceral) adiposity also increases BMI but is a strong negative factor for cardiometabolic health.2